The Effects of the Thor Power Tool Decision on the LIFO/FIFO Choice. - Halperin, Robert M.; Lanen, William N. (The Accounting Review, 1987)
ABSTRACT: This note examines the extent to which firms affected by a change in the tax law respond by making changes in the accounting methods used for financial reporting. The specific tax issue considered is the Thor Power Tool case that limited the use of formula write-downs for inventories. Since LIFO could be approximated by formula write-downs, we hypothesize that affected firms will tend to switch to LIFO during 1979 (and only during 1979) for tax reporting purposes and (because of the LIFO conformity rule) for financial reporting purposes as well. The empirical analyses of inventory method changes are consistent with this hypothesis.